What determines violence among female sex workers in an intimate partner relationship? Findings from North Karnataka, south India - Prakash Javalkar; Lucy Platt; Ravi Prakash; Tara Beattie; Parinita Bhattacharjee; Raghavendra Thalinja; Kavitha D. L.; Chaitanya AIDS Tadegattuva Mahila Sangha; Satyanarayana Ramanaik; Martine Collumbien; Calum Davey; Stephen Moses; et al. (BMC, 2019)
Abstract Background Like other women in India, female sex workers (FSWs) frequently experience violence from their intimate partners (IPs)-a reality that increases their risk of acquiring HIV or other sexually transmitted infections. Less is known about the nature of these intimate relationships or what aspect of the relationship increases the risk of IP violence (IPV). We measured the prevalence and determinants of IPV on FSWs in the context of north Karnataka, India, characterized by high HIV-prevalence and extreme poverty. Methods Overall 620 FSWs with an IP participated in a baseline survey conducted for an on-going cluster-randomised controlled trial aiming to evaluate the impact of a multi-level intervention on IPV reduction. We characterize the nature of intimate relationships and explored determinants of severe physical and/or sexual IP violence using univariable and multivariable analyses. Results The median age of participants was 35 years with 10 years of duration in an intimate relationship. Though most relationships originated from a sex work encounter, 84% stated that IPs did not know they were currently practicing sex work. In past 6 months, the experience of emotional violence was 49% (95%CI:45.2-53.2), physical 33% (95%CI:29.5-37.1) and sexual violence 7% (95%CI:4.8-8.9), while 24% (95%CI:21.0-27.9) FSWs experienced recent severe physical and/or sexual violence from IPs. Factors associated with recent IPV included experience of physical and/or sexual violence from their clients in last 6 months (AOR 2.20; 95%CI: 1.29-3.75), sexual intercourse in the past 1 month when their IP was under the influence of alcohol (AOR 2.30; 95%CI: 1.47-3.59) and providing financial support to their IP (AOR 2.07; 95%CI: 1.28-3.34). Conclusions The association between increased risk of violence and provision of financial support to an IP is indicative of gendered power dynamics as men remain dominant irrespective of their financial dependency on FSWs. Interventions are needed that address inequitable gender norms which makes FSWs tolerate violence even though she is not financially dependent on IP. Higher likelihood of violence in presence of alcohol use and FSWs' previous experience of workplace violence linked to IPV call for strengthening the crisis management systems within community-based organisations that can address all forms of violence and associated risk factors. Trial registration Clinical Trials NCT02807259